Microfluidic chip-inductively coupled plasma mass spectrometry for trace elements and their species analysis in cells. Issue 3 (16th March 2019) - He, Man; Chen, Beibei; Wang, Han; Hu, Bin
Abstract: Accurate identification and quantification of trace elements and their species in cells is an important prerequisite for the exploration of their physiological function and related mechanisms of process involving trace elements/species in human body. Inductively coupled plasma mass spectrometry (ICP-MS) is a powerful analytical instrument for trace elements detection, while it still suffers from insufficient limits of detection, interference from complex cell matrix, and incompatible sample consumption in cells analysis. Microfluidic chips which possess advantages of low sample/reagent consumption, rapid analysis speed and high spatial resolution provide perfect miniaturized and integrated platforms for cell analysis. In this article, microfluidic chip-ICP-MS techniques for trace elements and their species analysis in cells were reviewed. Both chip-based pretreatment techniques (e.g., magnetic solid phase microextraction (MSPME), monolithic capillary microextraction (MCME), liquid phase microextraction (LPME)) including chip-based array microextraction techniques for trace elements and their species analysis and droplet chip for single cell analysis were introduced. The newly developed methods of microfluidic chips in combination with ICP-MS for trace elements and their species analysis in small numbers of cells and even single cell were critically discussed, including chip-based MSPME/MCME/LPME-(electrothermal vaporization-ICP-)MS, on-line chip-based array MSPME/MCME-ICP-MS, on-line chip-based array MSPME-high performance liquid chromatography-ICP-MS and online droplet chip-time-resolved ICP-MS. These methodologies were demonstrated with high sensitivity, high throughput, good matrix resistance and low sample/reagent consumption, contributing to the quantification of trace elements/species in cells and even single cells. Relevant 20 references are included herein, and the development trend of microfluidic chip-ICP-MS techniques for cells analysis is prospected.